2008
DOI: 10.1243/09544119jeim311
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of pulsatile haemodynamic forces in a model of a bifurcated stent graft for abdominal aortic aneurysm repair

Abstract: The longitudinal haemodynamic force (LF) acting on a bifurcated stent graft for abdominal aortic aneurysm repair has been estimated previously using a simple one-dimensional analytical model based on the momentum equation which assumes steady flow of an inviscid fluid. Using an instrumented stent-graft model an experimental technique was developed to measure the LF under pulsatile flow conditions. The physical stent-graft model, with main trunk diameter of 30mm and limb diameters of 12 mm, was fabricated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…It has previously been shown that the drag force acting on an implanted stent-graft is largely dependent on the pressure acting on the graft. 44 In this study, the systolic pressure was increased by 16.6%, so the drag was also increased by a similar percentage; this caused ,13% reduction in the displacement force.…”
Section: ¤ ¤supporting
confidence: 51%
See 1 more Smart Citation
“…It has previously been shown that the drag force acting on an implanted stent-graft is largely dependent on the pressure acting on the graft. 44 In this study, the systolic pressure was increased by 16.6%, so the drag was also increased by a similar percentage; this caused ,13% reduction in the displacement force.…”
Section: ¤ ¤supporting
confidence: 51%
“…8,9 It has been hypothesized that excessive oversizing can lead to proximal aneu- rysm neck dilatation after EVAR and can greatly increase the risk of migration. 44 Because of this, the current practice is to oversize stent-grafts by 10% to 20% in vivo. 34 The oversizing of the devices in the current study was 16.66% in the aneurysm neck and in the iliac legs, which is more representative of the situation of a stent-graft implanted in the human aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Only Šutalo and colleagues and Zhou and colleagues compared theory with force measurements, but they made no comparisons with CFD-predicted forces. 13,14 Stent graft designers must allow for fatigue factors when using the peak forces in their design calculations because the forces will still be applying for 10 years. Engineers should not compromise structural strength, which includes the safety margin for fatigue and peak performance, to reduce the size for delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The other two studies that have compared theory with force measurements also used rigid stent graft models. 13,14 We assumed a parabolic input velocity profile with the justification that Morris and colleagues found that the input velocity profile did not affect the magnitude of the drag forces. 21 We assumed that the graft was oriented horizontally for our comparison, which is approximately equivalent to the case when a patient is lying down.…”
Section: Discussionmentioning
confidence: 99%
“…However, one cannot apply causation based on the similarity of observed trends. There are very few experimental in vitro studies available to which we can compare CFD results, and the studies that are available do not use parameters and conditions comparable to those that CFD studies attempt to simulate [23,37]. Even within the literature on CFD of stent-graft blood flow, the geometries (dimensions) as well as the boundary conditions and blood physical properties vary widely, as presented in Tables 1 and 3.…”
Section: Validitymentioning
confidence: 99%